Observation of H2O in a strongly lensed Herschel-ATLAS source at z=2.3 - Omont, A; Neri, R; Cox, P; Lupu, R; Guelin, M; van der Werf, P; Weiss, A; Ivison, R; Negrello, M; Leeuw, L; Lehnert, M; Smail, I; et al. (2011)
The Herschel survey, H-ATLAS, with its large areal coverage, has recently discovered a number of bright, strongly lensed high-z submillimeter galaxies. The strong magnification makes it possible to study molecular species other than CO, which are otherwise difficult to observe in high-z galaxies. Among the lensed galaxies already identified by H-ATLAS, the source J090302.9-014127B (SDP.17b) at z = 2.305 is remarkable because of its excitation conditions and a tentative detection of the H2O 202-111 emission line (Lupu et al. 2010, ApJ, submitted). We report observations of this line in SDP.17b using the IRAM interferometer equipped with its new 277-371 GHz receivers. The H2O line is detected at a redshift of z = 2.3049 ± 0.0006, with a flux of 7.8 ± 0.5 Jy km s-1 and a FWHM of 250 ± 60 km s-1. The new flux is 2.4 times weaker than the previous tentative detection, although both remain marginally consistent within 1.6σ. The intrinsic line luminosity and ratio of H2O(2 02 - 111)/CO(8 - 7) are comparable with those of the nearby starburst/enshrouded-AGN Mrk 231, and the ratio I(H2O)/L FIR is even higher, suggesting that SDP.17b could also host a luminous AGN. The detection of a strong H2O 202 - 1 11 line in SDP.17b implies an efficient excitation mechanism of the water levels that must occur in very dense and warm interstellar gas probably similar to Mrk 231. © 2011 ESO.